The Assessment of Relationship Between Interictal EEG Analysis and Seizure Prognosis - Koçer, Abdulkadir; İnce, Nurhan; Gözke, Eren; Çubuk, Ayşegül Derelioğlu; Çağırıcı, Sultan (Fırat University, 2006)
Objectives: To examine the relationship between EEG attributes and clinic attacks, and to define the value of inter-ictal EEG observation in defining the prognosis. Materials and Methods: Seventy four patients registered at PTT Training Hospital Neurology Clinic Epilepsy unit and 387 EEG belonging to them were evaluated retrospectively and prospectively. An EEG examination was accepted abnormal if it included epileptiform activity, slow wave, amplitude anomalies, or if resembled normal activity but displayed certain patterns indicating deviations in frequency, reactivity, dispersion and in other attributes. A decrease of more than 50% in normal or inter-ictal epileptiform activities, or in above mentioned EEG abnormalities was accepted as an improvement in EEG pattern. Ability to control clinically defined attacks (no attacks experienced by the patient) or a decrease of more than 75% compared to the period before the initiation of medication are accepted as indicators of good prognosis. Results: Our study group comprised 36(48.6%) female and 38(51.4%) male patients, with a mean age of 21.62±12.72 (R:9–78). Of 26 subjects with good prognosis, betterments were observed during EEG examinations in inter-ictal activities in 16(%44.4). Twenty (55.6%) subjects among 48 patients with bad prognosis were observed to have betterments in inter-ictal activities. Relations between EEG findings and prognosis were evaluated via chi-square tests. There was no statistically significant difference between percentage rates (P=0.103). Conclusion: Inter-ictal EEG attributes may give information about the prognosis and the presence of clinic attacks. The analysis is more valuable in adult patients without any associated pathology. It was suggested that studies with a greater number of patients examining a greater number of EEGs is required. ©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: EEG özellikleriyle klinik nöbet arasındaki ilişkiyi incelemek ve interiktal EEG takibinin prognozu saptamada değerini ortaya koymak. Gereç ve Yöntem: PTT Eğitim Hastanesi Nöroloji Kliniği Epilepsi ünitesince kayıtları bulunan 74 hasta ve bu hastalara ait 387 EEG geriye ve ileriye dönük olarak değerlendirildi. Bir EEG incelemesi; epileptiform aktivite, yavaş dalga, amplitüd anormallikleri ya da normal aktiviteyi andıran ancak, frekans, reaktivite, dağılım ve diğer özelliklerinde sapma gösteren belirli paternleri kapsıyorsa anormal kabul edildi. Normal ya da interiktal epileptiform aktivitelerde ya da yukarıda adı geçen EEG anormalliklerinde %50'den fazla azalma olması EEG paterninde düzelme olarak not edildi. Klinik olarak tanımlanan nöbetlerin kontrol altına alınabilmesi (hastanın hiç nöbet geçirmemesi ) veya nöbet sayısında ilaç kullanımı öncesine kıyasla %75'den fazla azalma gözlenmesi iyi prognoz göstergesi olarak kabul edildi. Bulgular: Çalışma grubumuz yaş ortalaması 21.62±12.72 (R:9–78) yıl olan 36(%48.6) kadın ve 38(%51.4) erkek hastadan oluşmaktaydı. Prognozu iyi olan 26 olgunun 16(%44.4)'sında EEG incelemesinde interiktal aktivitelerde düzelme izlendi. Prognozu kötü olan 48 olgunun 20(%55.6)'sinde EEG incelemesinde interiktal aktivitelerde düzelme izlendi. EEG bulguları ve prognoz arasındaki ilişki ki-kare testi ile değerlendirildi. Yüzde oranlar arasındaki farklılık istatistiksel olarak anlamlı bulunmadı (P=0.103). Sonuç: İnteriktal EEG kayıtlarındaki düzelmenin not edilmesi hastaların prognozu ve nöbet kontrolü hakkında bilgi verebilir. Hastaların erişkin yaş grubunda olması ve eşlik eden patoloji olmaması EEG analizini daha değerli kılacaktır. Daha çok hasta ve daha fazla sayıda EEG incelemesiyle yapılacak çalışmalara ihtiyaç olduğu düşünüldü. ©2006, Fırat Üniversitesi, Tıp Fakültesi
Epilepsi Hastalarında İnteriktal EEG ve Nöbet Prognozu Arasındaki İlişkinin Araştırılması